Thermo-Mechanical Properties Evaluation of Fiber-Reinforced Rubberized Concrete Mixes for Airfield Pavements - Zainab Abd Elshafy; Mohamed Mohamed; Ghada Moussa; Mahmoud Enieb; Elsayed Abdallah (JES: Journal of Engineering Sciences)
In response to the dual challenges of environmental degradation and occupational health hazards posed by emissions from conventional paving equipment, this study investigates sustainable alternatives for rigid pavement construction Fiber-Reinforced Rubberized concrete. Two hundred and thirty concrete specimens incorporating recycled rubber and various fibers were evaluated to develop environmentally friendly and durable pavement materials. Key performance indicators included ultrasonic pulse velocity (UPV) and abrasion resistance, focusing on acoustic damping characteristics, long-term durability, and preventive maintenance potential. Additionally, the impact of repeated thermal cycles was assessed to simulate field conditions. The results demonstrate that integrating rubber and fibers significantly enhances UPV and abrasion resistance. Furthermore, fiber-reinforced rubberized mixes exhibited superior performance retention after thermal cycling compared to conventional concrete pavements, indicating their viability for next-generation green infrastructure. The integration of recycled rubber and fibers into pavement construction is a crucial step toward reducing waste and minimizing the environmental footprint of the construction industry. This approach also has the potential to improve working conditions for construction workers by reducing exposure to hazardous emissions.